2011
DOI: 10.1016/j.mcn.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fusion for gene delivery to SCA1 affected Purkinje neurons

Abstract: Cerebellar Purkinje neurons (PNs) possess a well characterized propensity to fuse with bone marrow-derived cells (BMDCs), producing heterokaryons with Purkinje cell identities. This offers the potential to rescue/repair at risk or degenerating PNs in the inherited ataxias, including Spinocerebellar Ataxia 1 (SCA1), by introducing therapeutic factors through BMDCs to potentially halt or reverse disease progression. In this study, we combined gene therapy and a stem cell-based treatment to attempt repair of at-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 73 publications
(89 reference statements)
0
28
1
Order By: Relevance
“…Moreover, we observed fusion occurring within 2 weeks after the hfMSC transplantation into the cerebella, which is far earlier than the fusion resulting from intravenous injection of bone marrow derived cells (BMDCs) (at least 24 weeks) [48]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we observed fusion occurring within 2 weeks after the hfMSC transplantation into the cerebella, which is far earlier than the fusion resulting from intravenous injection of bone marrow derived cells (BMDCs) (at least 24 weeks) [48]. …”
Section: Discussionmentioning
confidence: 99%
“…The fusion of peripheral stem cells with PCs has mainly been studied using BMDCs [22,48,5053]. For example, Alvarez-Dolado et al have convincingly demonstrated fusion of BMDCs with PCs through transplantation of BMDCs expressing Cre and GFP into the peripheral circulation of lethally irradiated R26R transgenic mice expressing LacZ after Cre/lox recombination, although the frequency was very low [48,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is within the same tumor as well, creating opportunities for CSC populations with different CD markers to occur within the same tumor, making isolation and treatment of CSCs very arduous if based on these markers alone. The fusion of bone marrow derived cells (BMDCs) have been shown to occur with Purkinje neurons, cardiomyomycytes, and hepatocytes with evidence that trans-differentiation occurred only in these fused cells (AlvarezDolado et al, 2003;Chen et al, 2011). Trans-differentiation is a key characteristic of many tumors Shekhani et al, 2013).…”
Section: Theories Of Carcinogenesismentioning
confidence: 99%
“…Thus far, approaches have been based on surgical reconnection of transected mammalian nerve fibres, combined with the application of polymers such as polyethylene glycol (PEG) [72][73][74][75][76][77] . The mechanism through which PEG acts is not clear, but it is proposed to work like a fusogen by facilitating membrane merging 72 .…”
Section: Discussionmentioning
confidence: 99%